Public Perception of Sustainable Island Regional Development: A Case Study on Raijua Island - Kristian D Rupidara; Fredrik Lukas Benu; Hamza Huri Wulakada (Journal of Political and Governance Studies, 2025)
Background This study examines the perceptions of the Raijua Island community regarding the challenges of sustainable development in a small and remote island context, focusing on community participation and local wisdom as socio-cultural capital. Methods This study used a qualitative case study approach to understand the Raijua Island community's perceptions and practices regarding sustainable development. Data were collected through in-depth interviews, focus group discussions, and participatory observation. These data were then analyzed using thematic analysis with inductive coding and categorization. The validity of the findings was ensured through source and method triangulation, as well as member checking. Results The findings suggest that the inhabitants of Raijua Island interpret sustainable development as a means to address fundamental needs, including access to essential resources such as clean water, electricity, and infrastructure, while maintaining adherence to traditional values and ecological equilibrium. Local wisdom, encompassing traditional agricultural calendars, seasonal marine harvesting regulations, and lontar palm management, functions as an adaptive mechanism in response to limited natural resources and climate change. Conclusion Community participation, particularly through customary deliberations, plays a crucial role in sustaining social and environmental harmony. These findings underscore the necessity of locally grounded and participatory sustainable development in small islands, ensuring alignment with the cultural and ecological context of the community.